2010
DOI: 10.1063/1.3501122
|View full text |Cite
|
Sign up to set email alerts
|

p-type conductivity in silicon nanowires induced by heterojunction interface charge transfer

Abstract: p-type conductivity in intrinsic silicon nanowires (SiNWs) synthesized by an etching method was achieved via surface coating of MoO3 and tetrafluoro-tetracyanoquinodimethane thin layers. Characterization of field-effect transistors fabricated from single SiNW revealed a decrease in resistivity by six orders of magnitude and an increase in hole concentration by eight orders of magnitude with respect to the original silicon wafers. The enhancement of p-type conduction was demonstrated to originate from the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…Accumulation and depletion of electrons in MoS 2 by SCTD resulted in the shift of peak position as well as the change in emission intensity. SCTD on the 2D materials of graphene and MoS 2 revealed that the influence depth of surface dopants in the perpendicular direction was ca. 1.5 nm, corresponding to 2–4 layers of the 2D materials. Although the SCTD scheme has been demonstrated to be effective for 2D materials, little work has been implemented for other low-dimensional nanostructures such as semiconductor nanowires (NWs) and nanoribbons (NRs), presumably due to the relatively large diameter/thickness of these nanostructures.…”
supporting
confidence: 90%
“…Accumulation and depletion of electrons in MoS 2 by SCTD resulted in the shift of peak position as well as the change in emission intensity. SCTD on the 2D materials of graphene and MoS 2 revealed that the influence depth of surface dopants in the perpendicular direction was ca. 1.5 nm, corresponding to 2–4 layers of the 2D materials. Although the SCTD scheme has been demonstrated to be effective for 2D materials, little work has been implemented for other low-dimensional nanostructures such as semiconductor nanowires (NWs) and nanoribbons (NRs), presumably due to the relatively large diameter/thickness of these nanostructures.…”
supporting
confidence: 90%
“…g) XPS spectra of Si 2p peak for F4‐TCNQ on Si NWs with increasing thickness. g) Reproduced with permission . Copyright 2010, American Institute of Physics.…”
Section: Sctd In 1d Nanostructuresmentioning
confidence: 99%
“…To this end, solid organic or inorganic molecules with appropriate band energy levels are promising candidates. It has been reported that stable p‐type SCTD in Si NWs can be achieved via surface coating with F4‐TCNQ or MoO 3 thin films, while an n‐type SCTD of Si NWs has been realized by the adsorption of organic cobaltocene (CoCp 2 *) molecules . Besides electrical characterization, the Si core‐level shift in photoelectron spectroscopy also revealed the efficient doping process induced by interfacial charge transfer.…”
Section: Sctd In 1d Nanostructuresmentioning
confidence: 99%
“…MoO x is also widely used to deplete surface layer in several kinds of materials such as intrinsic Si nanowires (SiNWs), SrTiO 3 or cubic boron nitride by interfacial charge transfer . Inversion layer, which is usually generated when the work function between semiconductor and contact layer has a large difference, have also been observed in MoO x /n‐Si heterocontact solar cell in recent research works .…”
Section: Introductionmentioning
confidence: 99%